"Why not bathe the baby today?": A qualitative study of thermal care beliefs and practices in four African sites. Issue 1 (December 2015) - Adejuyigbe, Ebunoluwa; Bee, Margaret; Amare, Yared; Omotara, Babatunji; Iganus, Ruth; Manzi, Fatuma; Shamba, Donat; Skordis-Worrall, Jolene; Odebiyi, Adetanwa; Hill, Zelee
Abstract Background Recommendations for care in the first week of a newborn's life include thermal care practices such as drying and wrapping, skin to skin contact, immediate breastfeeding and delayed bathing. This paper examines beliefs and practices related to neonatal thermal care in three African countries. Methods Data were collected in the same way in each site and included 16–20 narrative interviews with recent mothers, eight observations of neonatal bathing, and in-depth interviews with 12–16 mothers, 9–12 grandmothers, eight health workers and 0–12 birth attendants in each site. Results We found similarities across sites in relation to understanding the importance of warmth, a lack of opportunities for skin to skin care, beliefs about the importance of several baths per day and beliefs that the Vernix caseosa was related to poor maternal behaviours. There was variation between sites in beliefs and practices around wrapping and drying after delivery, and the timing of the first bath with recent behavior change in some sites. There was near universal early bathing of babies in both Nigerian sites. This was linked to a deep-rooted belief about body odour. When asked about keeping the baby warm, respondents across the sites rarely mentioned recommended thermal care practices, suggesting that these are not perceived as salient. Conclusion More effort is needed to promote appropriate thermal care practices both in facilities and at home. Programmers should be aware that changing deep rooted practices, such as early bathing in Nigeria, may take time and should utilize the current beliefs in the importance of neonatal warmth to facilitate behaviour change.